Imperfect Central Bank Communication: Information versus Distraction - Spencer Dale; Athanasios Orphanides; Pär Österholm (Uppsala University, Department of Economics, 2008)
Much of the information communicated by central banks is noisy or imperfect. This paper considers the potential benefits and limitations of central bank communications in a model of imperfect knowledge and learning. It is shown that the value of communicating imperfect information is ambiguous. If the public is able to assess accurately the quality of the imperfect information communicated by a central bank, such communication can inform and improve the public`s decisions and expectations. But if not, communi-cating imperfect communication has the potential to mislead and distract. The risk that imperfect communication may detract from the publics understanding should be considered in the context of a central banks communications strategy. The risk of distraction means the central bank may prefer to focus its communi-cation policies on the information it knows most about. Indeed, conveying more certain information may improve the public`s under-standing to the extent that it crowds out a role for communicating imperfect information.
urn:nbn:se:uu:diva-15632
Keywords: E52; E58; 330; Transparency; Forecasts; Learning; Zentralbank; Geldpolitik; Kommunikation; Unvollkommene Information; Theorie